INVESTMENT PROJECTION MODEL IN INDONESIA - Syarief Gerald Prasetya; Yustiana Wardhani (The Accounting Journal of Binaniaga, 2018)
The achievement of economic activities in a country is measured by the economic development which is the projection of an increasing output as well as the increasing of the revenue to the owner of the production factors. Either Local Investment contribution or Foreign Investment has been an important role to reach the economic development, in order to reach it, the estimation of investment requirement either local investment or foreign one has to be done. This research aims to find out the connection between invesment and economic development, the investment projection model, and the total amount of invesment for the economic development. The research method has applied an explanatory method. The connection between economic development and investment can be analyzed by Capital Output Ratio (COR) concept. Having had the different perspectives of time, it has caused that mostly COR on average has been applied only to measure the productivity of the investment activities at a certain year, however, MCOR is used as the tool to predict the future investment’s requirement and the economic development.Key words: investment, economic development, capital output ratio